The Restoring Ecological Health to Your Land Workbook - Apfelbaum, Steven I. (The Science and Practice of Ecological Restoration, 2012)
The Restoring Ecological Health to Your Land Workbook is the first practical guidebook to give restorationists and would-be restorationists with little or no scientific training or background the “how to” information and knowledge they need to plan and implement ecological restoration activities. The book sets forth a step-by-step process for developing, implementing, monitoring, and refining on-the-ground restoration projects that is applicable to a wide range of landscapes and ecosystems.   The first part of the book introduces the process of ecological restoration in simple, easily understood language through specific examples drawn from the authors’ experience restoring their own lands in southern and central Wisconsin. It offers systematic, step-by-step strategies along with inspiration and benchmark experiences. The book’s second half shows how that same “thinking” and “doing” can be applied to North America’s major ecosystems and landscapes in any condition or scale.   No other ecological restoration book leads by example and first-hand experience like this one. The authors encourage readers to champion restoration of ecosystems close to where they live . . . at home, on farms and ranches, in parks and preserves. It provides an essential bridge for people from all walks of life and all levels of experience—from land trust member property stewards to agency personnel responsible for restoring lands in their care—and represents a unique and important contribution to the literature on restoration.